PM chemical composition and oxidative potential of the soluble fraction of particles at two sites in the urban area of Milan, Northern Italy. (March 2016) - Perrone, Maria Grazia; Zhou, Jun; Malandrino, Mery; Sangiorgi, Giorgia; Rizzi, Cristiana; Ferrero, Luca; Dommen, Josef; Bolzacchini, Ezio
Abstract: Recent epidemiological evidence support the hypothesis that health effects from inhalation of air particles are governed by more than just particle mass, since specific chemical components have been identified as important contributors to mortality and hospitality admissions. We studied the chemical composition and the oxidative potential (OP) of total suspended particle (TSP) samples from Milan at two sites with different traffic loads: a site in the low emission zone (LEZ) and a traffic site (TR) outside. Two a-cellular assays; dithiothreitol (OP DTT ) and 2′, 7' dichlorofluorescin (OP DCFH ) were used to characterize the OP of the soluble fraction of particles. TSP samples from LEZ showed significantly lower concentrations of traffic-related chemical components compared to TR. The decrease in the concentrations from TR to LEZ was maximum for EC, with a LEZ/TR ratio of 0.64 (±0.18), and a significant reduction (p < 0.01) was also observed for PAHs (LEZ/TR = 0.73 ± 0.16), elements (Mn, Cu, Zn, Cd, Pb: LEZ/TR ranged between 0.64 and 0.82), OC (LEZ/TR = 0.85 ± 0.12) and NH4 + (LEZ/TR = 0.92 ± 0.07). OP measures, expressed as OP/m 3 or OP/mg, were comparable between sites both for OP DTT and OP DCFH, thus not showing any significant impact of local traffic on OP values at sites. OP DTT and OP DCFH showed contrasting seasonal and daily trends, indicating that the two a-cellular assays gave complementary information on the OP of particles in Milan. The two OP assays resulted to be sensitive to different chemical properties of PM samples. OP DTT correlated positively only with Global Radiation (Spearman's rs  = 0.38, p < 0.05), which could be considered as a proxy for high concentrations of secondary oxidizing organics, while OP DCFH was related to various PM chemical species, mainly correlated with total mass (rs  = 0.65; p < 0.01), elements (e.g. Zn, rs  = 0.67; As, rs  = 0.65; p < 0.01) and the sum of sulfate and nitrate (rs  = 0.63; p < 0.01), a proxy for secondary aerosol. Highlights: Chemical speciation and OP of urban PM in two sites and three seasons was measured. Concentrations of traffic-related PM chemical species at LEZ site were lower than at TR site. The oxidative potential (OP DTT and OP DCFH ) of PM was comparable at TR and LEZ. OP methods (DTT and DCFH) differed in respect to correlation with PM composition. OP DTT and OP DCFH can provide complementary information about the oxidative capacity of particles.